THE PROJECTED RATE OF COMPETENCE FORMATION AS A TOOL OF EDUCATIONAL MANAGEMENT OF ADVANCED LEVEL OF EDUCATION - L. V. Lvov (Obrazovanie i Nauka, 2017)
Introduction. Specially organized complex of the scientific research directed to obtaining the reliable advancing information about development of pedagogical members is necessary for the development of educational policy, the strategy of development for educational systems, and methods of management of quality of pedagogical activity at different stages of education. The result of the educational management of professional and educational process is caused by the quality of pedagogical design. In turn, the quality of pedagogical forecasting is a factor determining the overall effectiveness of management through the pedagogical design.The aim of this article is to describe the model that allows applying the rate of competence formation as a tool of educational management and providing the advanced level of education. Methodology and research methods are based on pre-competence and context approach, which supposes the content selection as a set of competencies and designing the educational and professional process with the use of the rate of formation of ability and readiness (competency) as a tool of teaching management.Results. The author states socio-pedagogical contradiction, which is in acute shortage of predictive tools in the management of the educational process. The article describes terminology and empirical mathematical models that underpin pedagogical management of the educational and professional training of students that provides the advanced level of formation of organizational and managerial competence.Scientific novelty. The author clarifies the concept of the advanced level of education; introduces the term of the rate of formation of competency; proposes a new model to solve the problem of predicting learning outcomes and timely management influence by managers of education at all stages of the design and functioning of the educational system in the conditions of implementation of competence-based approach in the higher school, providing the advanced level of education.Practical significance. Presented in the article the model and the methodology of its application can be used for the specification of functions of management of the educational and professional process in the design and diagnosis of the extent of achievement of objectives of teaching students’ organization and management activity of advanced level.